2013
DOI: 10.4102/sajip.v39i1.1090
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between employee satisfaction and organisational performance: Evidence from a South African government department

Abstract: Orientation: There appears to be a dearth of literature that addresses the relationship between employee satisfaction and organisational performance in South African public organisations. Motivation for the study: This study attempted to contribute to the discourse on the influence of human resources to organisational performance.Research purpose: The aim of this study was to analyse the relationship between employee satisfaction and organisational performance in a public sector organisation.Research design: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 55 publications
3
54
0
1
Order By: Relevance
“…Here it is imperative to point out that the relationship between job satisfaction and organisational performance is complex; the research on it is rare; and theoretical and practical studies have not yielded an unambiguous answer to the real nature and strength of the connection between job satisfaction and organisational performance. In fact, some authors have found a positive correlation between job satisfaction and organisational performance (Chan, Gee, & Steiner, 2000;Ellinger, Ellinger, Yang, & Howton, 2002;Huselid, 1995;Koys, 2001;Latif et al, 2015;Mafini & Pooe, 2013), whilst, on the other hand, some have not discovered any statistically significant correlation between these two variables (Daily & Near, 2000;Mohr & Puck, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Here it is imperative to point out that the relationship between job satisfaction and organisational performance is complex; the research on it is rare; and theoretical and practical studies have not yielded an unambiguous answer to the real nature and strength of the connection between job satisfaction and organisational performance. In fact, some authors have found a positive correlation between job satisfaction and organisational performance (Chan, Gee, & Steiner, 2000;Ellinger, Ellinger, Yang, & Howton, 2002;Huselid, 1995;Koys, 2001;Latif et al, 2015;Mafini & Pooe, 2013), whilst, on the other hand, some have not discovered any statistically significant correlation between these two variables (Daily & Near, 2000;Mohr & Puck, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was supported by a number of researchers [28,29] who found teamwork to play an important role in improving employee job satisfaction. Van Dick, Christ, Stellmacher, Wagner, Ahlswede, Grubba, Hauptmeier, Hoehfeld, Moltzen and Tissington [48] affirm that persons who are identified with their working group will conscientiously see their working situations and conditions in a positive manner, culminating into higher job satisfaction.…”
Section: Discussionmentioning
confidence: 53%
“…Some scholars have also provided evidence that greater levels of teamwork are associated with improved employee satisfaction, prompting them to work harder [29,30]. Musriha [31] reported that effective teamwork can improve job satisfaction.…”
Section: Teamworkmentioning
confidence: 99%
“…For instance, in a recent study, Mahembe and Engelbrecht (2014) observed that whilst organisational citizenship behaviours in the aggregate promote the effective functioning of an organisation, the current system in the South African government does not have an explicit or direct mechanism for recognising and rewarding such conduct. In a previous study, Mafini and Pooe (2013) acknowledged the importance of organisational citizenship behaviours in the South African government, but also noted that ineffective rewarding and recognition of outstanding employees still hinders the process, leading to low job performance. Naturally, employees are less motivated to exert organisational citizenship behaviours under such circumstances.…”
Section: Discussionmentioning
confidence: 99%